(untitled) (BISTUA Revista de la Facultad de Ciencias Básicas, 2025)
The contamination of ecosystems by plastic fragments smaller than 5 mm in length (microplastics, MPs) and Climate Change (CC) threaten the health of terrestrial and aquatic ecosystems, biodiversity, and human existence. Because both phenomena occur simultaneously on a global scale, it is interesting to investigate whether they influence each other. Therefore, this study reviewed the state-of-the-art on the effect of MPs on CC and discussed the possible mechanisms that lead MPs to promote CC. To this end, a bibliometric analysis was conducted with publications from the Scopus database, and the discussion was complemented with information from relevant articles on the relationship between MPs and CC. The results showed that this is a developing field of knowledge, framed in five to seven clusters of study areas: sustainability, climate change and marine life, effects on organisms, components transported by MPs, methods for chemical characterization of MPs, and effects on human health. Moreover, most analyses of MPs-CC interactions are based on theoretical assumptions supported by limited empirical evidence, generally focusing on a single component. However, the few empirical studies linking the two events demonstrate that MPs pollution can intensify CC by inducing greenhouse gas (GHG) emissions through alterations in the biogeochemical cycles of water and sediments in aquatic and terrestrial ecosystems. These findings highlight the urgent need for experimental and field research to quantify and clarify the underlying mechanisms of the bidirectional interaction of MPs and CC with the environment.